The impact of abandoned/disused marble quarries on avifauna in the anticline of Estremoz, Portugal: does quarrying add to landscape biodiversity?. (16th November 2016) - Germano, David; Machado, Rui; Godinho, Sérgio; Santos, Pedro
Abstract: Although the extractive operations of quarrying are often considered environmental threats, there is some evidence that abandoned quarries may have a significant positive impact on biodiversity by enhancing habitat quality for several species. In Estremoz Anticlinal, SE Portugal, many of the existing marble quarries have been inactive for decades and were abandoned without any restoration project in progress. The impact of quarry abandonment on avifauna diversity was assessed relative to reference conditions using adjacent rural fields as control areas. No significant differences were found in within-community diversity (alpha diversity) between abandoned quarries and reference sites. However, several dissimilarity indices showed a clear divergence in species composition between abandoned quarries and reference sites. Furthermore, statistically significant differences in species compositions were found between quarries abandoned for different periods. Over time, species composition becomes more similar to that observed in reference sites, reflecting ecological succession and landscape resilience to quarrying. Nevertheless, the studied quarrying landscape exhibited higher gamma and beta diversity than the former traditional landscape; thus, our results suggest that abandoned quarries, rather than damaging and destroying niches, can promote new ecological niches and significantly diversify rural landscapes.